Thermodynamic evaluation of intermolecular interaction selectivity in separation of binary mixtures based on the activity coefficients at infinite dilution - Bakusele Kabane; Balungile Gasa; Nirmala Deenadayalu (Chemical Thermodynamics and Thermal Analysis, 2025)
Thermodynamic evaluation of deep eutectic solvents in separation of binary mixtures is increasing, and this is due to an easy preparation of deep eutectic solvents and their properties can be altered by different combinations of hydrogen bond acceptor to hydrogen bond donor. This study presents the intermolecular interactions between the prepared deep eutectic solvent with volatile organic solvents at different temperatures, T = (313.15 – 353.15) K and at atmospheric pressure. The investigated solvents were prepared by the combination of tetrabutylammonium acetate as hydrogen bond acceptor and ethylene glycol or diethylene glycol as hydrogen bond donor at a molar ratio of 1:3, respectively. The influence of hydrogen bond donor in separation of binary mixtures was evaluated and discussed. The intermolecular interactions of the prepared deep eutectic solvents with volatile organic solvents were evaluated based on the activity coefficients at infinite dilution values measured by the use of gas liquid chromatography. Excess thermodynamic properties at infinite dilution including excess enthalpies, Gibbs free energies and entropies were computed to further elucidate the interactions between the systems. Selectivity and capacity values were calculated to determine the feasibility of the solvents in separating industrial binary mixtures. The solvents were found promising for the separation of close boiling point mixtures comprising alcohols.